Dampak perubahan firm size terhadap firm value dengan profitabilitas sebagai variabel intervening pada perusahaan sektor pertambangan - Rosid, Abdul (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of firm size on firm value with profitability as an intervening variable in mining sector companies. In this study there are three research variables, namely Company Size, Profitability, and Firm Value. Associative causality research method. This research was conducted on mining sector companies listed on the Indonesian stock exchange. Sampling used purposive sampling. The results showed that firm size had no significant effect on firm value, firm size had a positive and significant effect on profitability, profitability had a positive and significant effect on firm value, and profitability was able to mediate firm size on firm value.